Los discursos sobre el cuerpo en el currículo oficial: una aproximación al Diseño Curricular Nacional - Rosales Lassús, José Luis (2010)
Taking as an object of study the current official curriculum, this article analyzes the discourses of body underlying the curriculum. Five types of discourses have been identified: body that knows; expressive body; body as a trait of personality; universal body, and moving body. The study mentioned the changes of these discourses in relation with the different levels of the basic education (initial, primary, secondary).